Impact of tertiary Gleason pattern 5 on prostate cancer aggressiveness: Lessons from a contemporary single institution radical prostatectomy series - Zachary B. Koloff; Daniel A. Hamstra; John T. Wei; Jeffrey S. Montgomery; Scott A. Tomlins; Angela J. Wu; Todd M. Morgan; Javed Siddiqui; Kellie Paich; Arul M. Chinnaiyan; Felix Y. Feng; Alon Z. Weizer; et al. (Asian Journal of Urology)
Objective: To better evaluate tertiary Gleason pattern reporting and to evaluate the impact of tertiary Gleason pattern 5 (TP5) on prostate cancer pathological features and biochemical recurrence at our large single institution. Methods: We retrospectively reviewed 1962 patients who underwent radical prostatectomy (RP) for prostate cancer; TP5 was reported in 159 cases (8.1%). Men with Gleason score (GS) 7 and GS 8 disease were divided into subgroups with and without TP5, and histopathological features were compared. Multivariate analyses were conducted to assess the impact on TP5 on biochemical-free survival (BFS). Results: Tumors possessing GS 3 + 4 with TP5 were more likely to exhibit extraprostatic extension (EPE) and had a larger tumor diameter (TD) than GS 3 + 4 alone. GS 3 + 4 with TP5 was also associated with positive surgical margins (SM), seminal vesicle involvement (SVI), and higher pre-operative prostate-specific antigen (PSA) values, but without statistical significance. GS 4 + 3 with TP5 more commonly presented with EPE, positive SM, SVI, and greater TD and pre-operative PSA level than GS 4 + 3 alone. In multivariate analysis, Gleason score, EPE, and TP5 were overall independent risk factors for PSA recurrence in this cohort. Additionally, GS 4 + 3 with TP5 was associated with shorter time to recurrence versus GS 4 + 3 alone. Conclusion: Our results emphasize the importance of TP5 and suggest that criteria for tertiary pattern reporting in prostate cancer should be standardized. Further studies are needed to evaluate the role of tertiary patterns in prognostic models.